Landscape concept in photography: from Luigi Ghirri to Antonio Ottomanelli - Malavenda, Teodora (DISEGNARECON, 2014)
In the 80s of the last century the Italian photography, like other art forms, reflected the political, economic and cultural changes of the Nation. It was the time of a new documentary photography that investigated the transformation of the urban areas. Within this process the landscape was the subject of a new interpretation. In 2013 this process of documentation was worked out again, but in a modern way, by Antonio Ottomanelli. In his project "Collateral Landscape", he took pictures in different cities of the world such as Kabul, Baghdad, Sadr City, Herat, Dokan, New York, Gaza City. Distant places and only apparently different from each other. In fact, all of them have been destroyed by war or, in the case of New York, have been target of a terrorist attack.